Enhancement of aluminum tolerance in wheat by addition of chromosomes from the wild relative Leymus racemosus - Mohammed, Yasir Serag Alnor (Japanese Society of Breeding, 2013)
Aluminum (Al) toxicity is the key factor limiting wheat production in acid soils. Soil liming has been used widely to increase the soil pH, but due to its high cost, breeding tolerant cultivars is more cost-effective mean to mitigate the problem. Tolerant cultivars could be developed by traditional breeding, genetic transformation or introgression of genes from wild relatives. We used 30 wheat alien chromosome addition lines to identify new genetic resources to improve wheat tolerance to Al and to identify the chromosomes harboring the tolerance genes. We evaluated these lines and their wheat background Chinese Spring for Al tolerance in hydroponic culture at various Al concentrations. We also investigated Al uptake, oxidative stress and cell membrane integrity. The L. racemosus chromosomes A and E significantly enhanced the Al tolerance of the wheat in term of relative root growth. At the highest Al concentration tested (200 μM), line E had the greatest tolerance. The introgressed chromosomes did not affect Al uptake of the tolerant lines. We attribute the improved tolerance conferred by chromosome E to improved cell membrane integrity. Chromosome engineering with these two lines could produce Al-tolerant wheat cultivars.